Influence of cover crop termination timing on weed suppression in soybean (Glycine max) and corn (Zea mays) in Kansas - Chism, Luke Isaiah (My University, 2026)
Cover crops are becoming more commonly adopted throughout Kansas as a tool to help farmers manage weeds in soybean and corn crops. Though popularity continues to increase, there are still many questions and misunderstandings of the efficacy, profitability, and applicability of cover crops in real farm scenarios. More information is needed to provide quality recommendations to farmers and advisors in Kansas. The objectives of this research were to evaluate different cover crop (CC) termination timings relative to crop planting on weed suppression and grain yields in soybean and corn fields across various regions of Kansas. Additionally, the impact of residual herbicides at the time of CC termination on weed management in corn was evaluated. A total of 10 soybean and six corn on-farm and on-station field trials were conducted through the growing seasons of 2017 through 2020. Most sites had fall-seeded cereal (wheat, cereal rye, or triticale) as the CC, with one site using spring oat, which were terminated anywhere from 5 weeks before to 1 week after planting the cash crop. Cover crop termination was done with a glyphosate herbicide application at the appropriate timing. The results of all studies showed that delaying termination increased CC biomass at termination and reduced weed densities at 25 days after planting (DAP) the cash crop, especially compared to plots with no CC. For soybean, maximum CC biomass in 2018 was 989 g m⁻² in western KS when seeded after wheat harvest and terminated 1 week after soybean planting. In 2019, the maximum CC biomass was 1619 g m⁻² in eastern KS with a wet spring season. For corn at on-farm sites, where crop planting typically occurred between mid-April to mid-May, less total CC biomass was produced than before soybean which were planted later (late May to early June). In on-station studies, corn planting occurred later (late May to early June) and similar amounts of CC biomass were produced as in the soybean studies. By adding a residual herbicide at time of CC termination in corn, weed density by 25 DAP was the same as CC terminated at planting with no residual herbicide across the on-station studies. No differences in corn stands were observed with use of CC at any termination timing in on-station studies. Corn yield differences were observed at two of the six locations: at Oak Hill 2019 in the on-farm study and at Ashland Bottoms 2020 in the on-station study. Lowest corn yields were observed when CC termination was 2 weeks before planting (WBP) at Ashland Bottoms 2020 and at 2 WBP and 1 week after planting at Oak Hill 2019. Across all soybean studies, no yield differences were observed across CC termination times. Yields at each site differed based on potential for that area of Kansas. In conclusion, CC can be terminated later to maximize the positive response of increased biomass and reduced weeds with minimal impact on soybean and corn yields.
Keywords: Cover crop; Corn; Soybean; Palmer amaranth; Resistance; Termination